Fabrication of Closed Hollow Bulb Obturator Using Thermoplastic Resin Material - Bidhan Shrestha; E. Richard Hughes; Raj Kumar Singh; Pramita Suwal; Prakash Kumar Parajuli; Pragya Shrestha; Arati Sharma; Galav Adhikari (Case Reports in Dentistry)
Purpose. Closed hollow bulb obturators are used for the rehabilitation of postmaxillectomy patients. However, the time consuming process, complexity of fabrication, water leakage, and discoloration are notable disadvantages of this technique. This paper describes a clinical report of fabricating closed hollow bulb obturator using a single flask and one time processing method for an acquired maxillary defect. Hard thermoplastic resin sheet has been used for the fabrication of hollow bulb part of the obturator. Method. After fabrication of master cast conventionally, bulb and lid part of the defect were formed separately and joined by autopolymerizing acrylic resin to form one sized smaller hollow body. During packing procedure, the defect area was loaded with heat polymerizing acrylic resin and then previously fabricated smaller hollow body was adapted over it. The whole area was then loaded with heat cure acrylic. Further processes were carried out conventionally. Conclusion. This technique uses single flask which reduces laboratory time and makes the procedure simple. The thickness of hollow bulb can be controlled and light weight closed hollow bulb prosthesis can be fabricated. It also minimizes the disadvantages of closed hollow bulb obturator such as water leakage, bacterial infection, and discoloration.